Risk factors for major infections in Wegener granulomatosis: analysis of 113 patients. Issue 5 (26th May 2008) - Charlier, C; Henegar, C; Launay, O; Pagnoux, C; Berezné, A; Bienvenu, B; Cohen, P; Mouthon, L; Guillevin, L
Abstract : Objective: To characterise major infectious complications and analyse potential risk factors in patients with Wegener granulomatosis (WG). Methods: Data from 113 patients with WG (69 male) followed at least once between January 1984 and March 2006 in our internal medicine department, were analysed retrospectively. Results: A total of 35 patients (mean (SD) age at WG diagnosis: 50.2 (13.05) years) developed 53 major infections. Infections were: bronchopneumonias (n = 19), herpes zoster recurrences (n = 9), cellulitis (n = 4), prostatitis (n = 4), spondylodiscitis and septic arthritis (n = 3), digestive tract infections (n = 2), Enterococcus faecalis or Staphylococcus aureus septicaemia (n = 2), viral hepatitis B reactivations (n = 2), post transfusion HIV infection with fatal cerebral toxoplasmosis, oesophageal candidiasis, disseminated herpes simplex and cytomegalovirus infection, cytomegalovirus retinitis, herpetic keratitis, herpetic stomatitis, Serratia sp. node suppuration and fever resolving under broad spectrum antibiotics (n = 1 each). Half of the major infectious episodes occurred within 3 years after WG diagnosis. Eight (7%) patients died, with two (2%) infection-related deaths. Patients diagnosed with WG before 1996 had a significantly higher rate of infection than those diagnosed later (48% vs 24%, p = 0.02). Cyclophosphamide and corticosteroids were independently associated with significantly higher risk of major infection (p<0.05 and <0.001, respectively). All patients treated since 1993 received antipneumocystosis prophylaxis. Conclusion: Cyclophosphamide and corticosteroids were associated with higher risk of infection. Despite systematic cotrimoxazole prophylaxis, major infections, mostly bronchopneumonias and herpes zoster recurrences, were still common in the course of WG.